Liver enzymes in patients with chronic kidney disease undergoing peritoneal dialysis and hemodialysis (Clinics, 2012)
OBJECTIVE: The present study was designed to analyze the serum levels of aspartate and alanine aminotransferases, gamma-glutamyl transferase, and the hematocrit in patients with chronic kidney disease who were undergoing peritoneal dialysis or hemodialysis. PATIENTS AND METHODS: Twenty patients on peritoneal dialysis and 40 on hemodialysis were assessed, and the patients were matched according to the length of time that they had been on dialysis. Blood samples were collected (both before and after the session for those on hemodialysis) to measure the enzymes and the hematocrit. RESULTS: In the samples from the patients who were undergoing peritoneal dialysis, the aspartate and alanine aminotransferase levels were slightly higher compared with the samples collected from the patients before the hemodialysis session and slightly lower compared with the samples collected after the hemodialysis session. The levels of gamma-glutamyl transferase in the hemodialysis patients were slightly higher than the levels in the patients who were undergoing peritoneal dialysis. In addition, the levels of aminotransferases and gamma-glutamyl transferase that were collected before the hemodialysis session were significantly lower than the values collected after the session. The hematocrit levels were significantly lower in the patients who were on peritoneal dialysis compared with the patients on hemodialysis (both before and after the hemodialysis session), and the levels were also significantly lower before hemodialysis compared with after hemodialysis. CONCLUSION: The aminotransferase levels in the patients who were undergoing peritoneal dialysis were slightly higher compared with the samples collected before the hemodialysis session, whereas the aminotransferase levels were slightly lower compared with the samples collected after the session. The hematocrits and the aminotransferase and gamma-glutamyl transferase levels of the samples collected after the hemodialysis session were significantly higher than the samples collected before the session. Taken together, the present data suggest that hemodilution could alter the serum levels of liver enzymes.